Leave a light on – Terracotta lamps from Agia Paraskevi of Arachamitai, from the Classical period until Roman times - Lehikoinen, Maija (My University, 2016)
This thesis deals with terracotta lamps found at the archaeological site of Agia Paraskevi of Arachamitai during the years 2010–2014. The research questions are: What kind of lamps were used on the site and when? For what purposes were the lamps used? Where were they manufactured? In order to address these questions, a total of fifty lamps have been chosen to form the body of research material. To answer the first research question, a typology for these lamps has been created with twenty-one types and one variant, after examining various lamp typologies and previous publications. The find contexts and distribution of the lamps are both examined to test the dates for the different lamp types gathered from other publications, and to answer the question on what purposes the lamps were used on the site. Visual observation of the clay of the lamps and information on clay materials from other sites are both examined to determine the lamps' origins. The lamps in this study date from the 5th century BC to the 2nd century AD. The find contexts allow the dating of the lamps according to the other publications, but suggestions of more site-specific dates are given to some lamps. The distribution of the lamps indicates that while most were used for everyday lighting at the sanctuary, some may have had ritual connections. Most of the lamps were manufactured locally or at a nearby Arcadian site. Few lamps can be regarded as imports.